Inventario de yacimientos de arcillas con potencialidades para ser utilizadas como material impermeabilizante en reservorios para cosecha de agua en el sector rural del cantón Loja - Herrera Soto, Jenny Gabriela (2024)
Clay is a highly exploited mineral due to its numerous uses in the industrial sector, particularly for construction, agriculture, and medicinal purposes. Consequently, a study was conducted to characterize the soils of the Gonzanamá Cantón, to determine their suitability for pond impermeabilization. This thesis aims to develop a strategic inventory of clays in the Loja Canton with impermeabilizing potential for reservoir construction. The study was divided into three phases: pre-field, field, and office. In the first phase, areas with significant clay soil in the parishes of Loja canton were identified. During the second phase, in situ we help using GPS were conducted to obtain the coordinates of each site. The final phase involved generating maps for each parish in Loja Canton and creating the clay inventory. The results indicate that 37 outcrops were identified across three zones: northeast, northwest, and south. Additionally, different geological characteristics were found due to climatic variations in each zone. Furthermore, 12 georeferenced maps of the 37 outcrops in the parishes of Loja Canton were produced. Finally, an inventory of soils with the best physico-mechanical characteristics was created, revealing that the northwestern zone has clay content ranging from 38.40% to 67.60%, while the northeastern zone has clay content ranging from 34.40% to 39.80%. The liquid limit percentages range from 52.87% to 84.06%, and the plastic limit percentages range from 19.30% to 50.44%. Additionally, clay activity values range from 0.6 to 0.92. These characteristics are ideal for use as impermeabilizing material in reservoir construction.